Ordinance no. 25, OXFORD EAGLE, Jul. 7, 1898, at 2 (Oxford, Mississippi) - (:unkn) unknown (General Publisher, 1898)
Any marshal or night-watchmen who fails or refuses to report, arrest, or bring to trial anyone who has violated any ordiannce of the town shall be guilty of a misdemeanor and fined twenty-five dollars.
--
Keywords: PEACE OFFICERS